Parasitological research in Antarctica: review of the issues and future prospects - Y. Kvach; T. Kuzmina (Ukrainian Antarctic Journal, 2020)
This paper provides an overview of parasitological research conducted in Antarctica, particularly near the Ukrainian Antarctic Akademik Vernadsky station. Taking into account the global climate and anthropogenic changes that lead to the destruction of natural ecosystems of the Southern ocean and the abundance of fish parasites of zoonotic significance posing a threat to human health, investigations of the animal parasite communities in the Antarctic, including in the teleost fishes, become of special relevance. Further long-term ecological and parasitological monitoring of Antarctic marine and coastal ecosystems is necessary and will allow to investigate the speed and directions of ecological changes in Antarctic marine ecosystems.